Ancient Engineers' Inventions Precursors of the Present - Rossi, Cesare; Russo, Flavio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the inventions and designs of ancient engineers who are the precursors of the present. The period ranges mainly from 300 B.C. to 1600 A.D. with several exceptions. Many of the oldest inventions are documented by archaeological finds, often very little known, mainly from Pompeii, Herculaneum and Stabiae and reveal a surprising modernity in their conception. Most of the inventions presented in the first four parts of the book were conceived up to the late Roman Empire and may be considered as milestones, each in their respective field. The fifth part concentrates on more recent centuries. The sixth part deals with some building construction techniques. Generally, for each of the presented inventions, three elements of research and reference are provided: written documents (the classics), iconic references (coins, bas-reliefs, etc.) and archaeological findings. The authors did not write this book for engineers only; hence they describe all thedevices without assuming wide technical knowledge. The authors' main aim is to try to communicate their enthusiasm for the inventions and the inventors of the past and to contribute to the fascinating study of the History of Engineering. This second edition includes new topics and chapters that are of special interest to engineers.
Premise: Representing and Measuring the Environment -- A premise: it all started with a drawing -- I.1 Elevations, Plan and Sections -- I.2 Protohistoric Drafting machine for the clay tablets engraving -- I.3 Examples of planimetries from the IV millennium B.C. to the I century A.D. -- I.4 Ancient Units -- 1. Measuring Mass -- Introduction -- 1.1 The balance scale -- 1.2 The steelyard balance -- Observations -- 2 Measuring Distance and Slope -- Introduction -- 2.1 Jacob's staff -- 2.2 Range finders -- 2.3 The Astrolabe -- 2.4 The dioptre by Heron -- 2.5 The ancient odometers -- Observations -- Measuring a building height by an astrolabe -- Measuring the distances by the groma and by the surveyor's cross -- 3 Measuring Time -- Introduction -- 3.1 The sundial -- 3.2 Water clocks -- Observations -- 4 Orientation -- Introduction -- 4.1 The Sundial Compass -- 4.2 The Chinese South-Pointing Chariot Sundial Compass -- 4.3 The Windrose and the Magnetic Compass -- 5 Ancient Computation Devices -- Introduction -- 5.1 The Abacus -- 5.2 The Mesolabio -- 5.3 The Mechanism of Antikitera -- Observations -- 6 The Natural Energy Used In Antiquity -- Introduction -- 6.1 Energy from man -- 6.2 Energy from animals -- 6.3 The capstan -- 6.4 The treadwheel -- 6.5 Rough evaluation of the power from a wind motor -- 6.6 Rough evaluation of the power from a waterwheel -- 7 Wind Motors -- Introduction -- 7.1 The wind mills -- 7.2 Wings on the sea: the sails -- 7.3.3 The Flettner rotor -- Observations -- 8 Hydraulic Motors -- Introduction -- 8.1 Water wheels with vertical axis -- 8.2 Water wheels with horizontal axis -- 8.3 The floating mill -- 8.4 Water wheels in the Middle Ages and the Renaissance -- Observations -- 9 Refrigeration and Heating -- 9.1 Air Cooling with Wind Towers -- 9.2 The production of ice -- 9.3 Nero's Sherbet -- 9.3 Wheat Pits -- 9.4 Heating and Thermal Baths -- 9.5 Energy Saving: the Sun Chimney Heating and Thermal Baths -- 10 The Production Of Water -- 10.1 The Air Well -- 10.2 The DewBasin -- 10.3 The Qanat -- 10.4 Distillation -- 11 Lifting Water -- Introduction -- 11.1 The early devices -- 11.2 The Archimedes' screw -- 11.3 Norias -- 11.4 Pumps -- Observations -- 12 Adduction and Distribution of Water -- Introduction -- 12.1 Open ducts -- 12.2 Penstocks -- 12.3 The great cisterns -- 12.4 Water distribution systems -- 12.5 Pipes -- 12.6 Valves -- 12.7 Hydraulic mining -- Observations -- 13 Underwater Activities -- Introduction -- 13.1 Scuba divers -- 13.2 Diving bell -- 14 Transports -- Introduction -- 14.1 Roman charts -- 14.2 Railed cargo -- 14.3 The rails of Pompei -- 14.4 Ancient self-propelled vehicles -- 14.5 Early ball bearings -- 14.6 Transport on water -- 14.7 Cableways -- 14.10 The dawn of the flight in the antiquity -- Observations -- 15 Telecommunications -- Introduction -- 15.1 Acoustic -- 15.2 Carrier pigeons -- 15.3 Optical telecommunication systems -- 15.4 Lighthouses -- 15.5 The water telegraph -- Observations -- 16 Medicine and Health -- Introduction -- 16.1 Medical Assistance provided to Legionnaires -- 16.2 Reconstructive Plastic Surgery -- 16.3 Early Penicillin -- 16.4 The Beginning of Biological Warfare -- 17 Secondary Motors -- Introduction -- 17.1 Cranes and tackle -- 17.2 Gravity driven elevators -- 17.3 Siege towers -- 17.4 The trebuchet -- 17.5 Flexion elastic motors -- 17.6 Torsion elastic motors -- 17.7 Throwing machines operated by torsion motors -- 17.8 Mechanics of the throwing machines -- 17.9 Pneumatic motors -- 17.10 Small spring motors -- 17.11 Ancient steam engines -- Observations -- 18 Spinnind and Weaving -- Introduction -- 18.1 The dawn of spinning and weaving -- 18.2 The spinning wheel -- 18.3 The mechanical spinning -- 18.4 The automatic weaving -- Observations -- 19 Some Applications of Fire -- Introduction -- 19.1 Fire ignition -- 19.1.2 Optical flints -- 19.2 Marine fire - the Roman candle -- 19.3 Wind lanterns -- 19.4 Fire for warming -- 19.5 Fire for warfare -- 19.6 The protection from fire: asbestos -- 20 Automata (Towards automation androbots) -- Introduction -- 20.1 The Hellenistic Age -- 20.2 The Middle Ages -- 20.3 The Renaissance -- 20.4 The XVIII Century -- 20.5 The XIX Century -- 20.6 Automata of the Far East -- 20.7 Between the two millenniums -- Observations -- 21 Some Ancient Building Techniques -- Introduction -- 21.1 Stone buildings -- 21.2 Concrete Buildings -- 21.3 Considerations on the polygonal work -- 21.4 Earthquake-resistant buildings with wooden ribs -- 21.5 Seismic isolators -- 21.6 Consideration on ancient concrete -- Subject Index. .
Keywords: Engineering design; Machinery; Technology; History; Archaeology; Science -- History; Engineering Design; Machinery and Machine Elements; History of Technology; Archaeology; History of Science